The Leakage Current Components as a Diagnostic Tool to Estimate Contamination Level on High Voltage Insulators - Ali A. Salem; R. Abd-Rahman; Samir Ahmed Al-Gailani; M. S. Kamarudin; Hussein Ahmad; Zainal Salam (IEEE Access, 2020)
The current paper presents an alternative and innovative technique to predict the severity of pollution of high voltage insulator using a higher harmonics component with up to the 7th component of leakage current. The leakage current was measured using a current transformer and a shunt resistor. Next, laboratory tests were conducted on glass and porcelain insulators with artificial pollution under salt-fog pollution state which is further represented by three levels, namely light, medium, and high contamination. In this case, the formulation of a new severity of harmonic index refers to a ratio of the sum of 5th and 7th to the 3rd harmonic component. More importantly, the new index managed to provide more accurate results when used as a diagnostic tool for the levels of pollution, compared to the ratio of the total harmonic distortion (THD) to the number of odd harmonics components (n) as the boundaries. In this case, the insulators were found to be in a clean and normal condition when the K(5+7)/3 value was greater than 3%. Contrastingly, the insulators were in an extreme condition when the K(5+7)/3 was lower than 3%. Nevertheless, there is a high probability of a flashover in glass and porcelain insulators if the K(5+7)/3 value is less than 2%. The present study shows the possibility of utilizing the value of strange harmonics up to the 7th component of leakage current as the parameter for the monitoring of leakage current in overhead insulators in the presence of contamination. Overall, it can be concluded that the 3rd, 5th, and 7th harmonics details extracted from the leakage current act as a good indicator for the level of contamination.